Biochemical and Toxicological Investigations of 5-Fluorouracil, Nimesulide, and Ascorbic Acid in Hepatocellular Carcinoma: Biochemical and Toxicological Investigations of 5-Fluorouracil, Nimesulide, and Ascorbic Acid in Hepatocellular Carcinoma - Hussain, Nazim (International Journal of Pharmaceutical & Biological Archive, 2020)
The objective of this study was biochemical and toxicological investigations of 5-fluorouracil (5-FU), nimesulide, and ascorbic acid (Vitamin C) in Wistar rats with hepatocellular carcinoma in. Results showed that DENA increased the level of alpha fetoprotein (AFP), alkaline phosphatase (ALP), serum glutamic oxaloacetate transaminase (SGOT), serum glutamic pyruvate transaminase (SGPT), and total bilirubin which was decreased by the various combinations of 5-FU to normal. On the other hand, DENA resulted in decrease of blood glucose level, DFN decreased more than DF, and DFC showed results similar to DFN, while DFNC led to increased AFP, ALP, SGOT, SGPT, and total bilirubin levels to normal. Histopathological evaluations showed normal architecture of tissues of rat liver in normal group. Lesser damage of hepatocytes and low index of necrosis were in pre- and post-treated group of 5-FU+DF, DFN+DFC groups. DFNC treated group exhibited histological features resembling normal control animals.